Problematika Pembiayaan Mudharabah di Perbankan Syariah Indonesia - A. Chairul Hadi (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
Islamic banks were originally constructed as a non-usury banking system with profit and loss sharing in all its operational mechanism. But in its development to meet the banking function as a financial intermediary, all types of businesses that legalized Islamic law (syari'a) based nonprofit- sharing, such as trade, rentals and other services into a product of Islamic banks. The problem then was the product of this result has not become the main business of Islamic banks. In theory, financing product with a profit sharing scheme can be more prosperous economic community. This paper will try to discuss about problems and solutions sharing system (mudaraba) in a financing scheme in Islamic banks.